Acupressure Effectiveness and Yoga Exercises To Reduce Menstrual Pain - Yasi Anggasari; Yunik Windarti (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Women of reproductive age more often use pharmacological therapy to treat dysmenorrhea. The aim of this study was to analyze the acupressure therapy sanyinjiao and Hegu with yoga exercises to reduce dysmenorrhea. This research involved 40 respondents, Definition in this study using two intervention groups, namely group therapy technique of acupressure and yoga exercise group. The results of statistical tests showed that the acupressure group experienced a significant decrease in pain scale, namely 3.35 compared to the yoga exercise group, which only experienced a decrease of 2.05 while the average value of the difference after acupressure and yoga exercise was -1.3 and Mann Whitney obtained p value = 0.001. So it was found that there was an average difference in group 1 and group 2 after the intervention where the yoga exercises Action was more effective than Acupressure in reducing dysmenorrhea.